2021
DOI: 10.3389/fimmu.2021.744425
|View full text |Cite
|
Sign up to set email alerts
|

Dietary β-Carotene on Postpartum Uterine Recovery in Mice: Crosstalk Between Gut Microbiota and Inflammation

Abstract: As the precursor of vitamin A, β-carotene has a positive effect on reproductive performance. Our previous study has shown that β-carotene can increase antioxidant enzyme activity potentially through regulating gut microbiota in pregnant sows. This study aimed to clarify the effect of β-carotene on reproductive performance and postpartum uterine recovery from the aspect of inflammation and gut microbiota by using a mouse model. Twenty-seven 6 weeks old female Kunming mice were randomly assigned into 3 groups (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…However, it has also been reported that the relative abundances of Erysipelotrichaceae (butyrate-producing bacteria) were negatively related to the expression of in ammatory cytokines [33]. Among Erysipelotrichaceae family, Faecalibaculum genus promotes SCFAs production, carbohydrate metabolism, and lactate metabolism [34]. A higher concentration of butyric acid improves the in ammation and oxidative stress of ALI by stimulating the secretion of IL-22 from intestinal epithelial cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been reported that the relative abundances of Erysipelotrichaceae (butyrate-producing bacteria) were negatively related to the expression of in ammatory cytokines [33]. Among Erysipelotrichaceae family, Faecalibaculum genus promotes SCFAs production, carbohydrate metabolism, and lactate metabolism [34]. A higher concentration of butyric acid improves the in ammation and oxidative stress of ALI by stimulating the secretion of IL-22 from intestinal epithelial cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that Firmicutes was often highly represented in the gut microbiota of healthy individuals and could be reduced with illness, while a significant increase in Proteobacteria abundance could lead to chronic abdominal pain/diarrhea and a series of gastrointestinal inflammations [ 46 48 ]. The phylum Bacteroidetes comprises bacteria that are common gut-associated microbes with a relatively high risk of causing diarrheal diseases and had a negative correlation with inflammatory cytokines [ 49 , 50 ]. The ratio of Firmicutes/Bacteroidetes is commonly used to evaluate various enteropathies of patients, such as irritable bowel syndrome, inflammatory bowel disease, and metabolic diseases [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the abundance of Coriobacteriaceae_UCG-002 and Enterorhabdus were significantly positively correlated with serum TC and TG levels, respectively. In addition, Abx treatment also decreased the abundance of Faecalibaculum and Desulfovibrio , which contribute to the production of pro-inflammatory cytokines [ 89 , 90 , 91 , 92 ] and then promote the development of metabolic dysfunction. Similarly, it has been demonstrated that Desulfovibrio can produce LPS and then induce inflammation and insulin resistance [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%